Komparasi Efektivitas dan Model Governance Inkubator Bisnis Digital antara Pengelola Pemerintah, BUMN, Swasta, Komunitas, dan Universitas - Suci Lestari Yuana; Nur Azizah; Indri Dwi Apriliyanti (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2016)
The growing number of incubator business and coworking spaces for digital business in Indonesia has raised critical question on its correlation with Indonesian competitiveness in IT industry. This paper attempts to analyze internal factors of each incubator model that drives innovation as well as to identify power relations of actors in IT ecosystem. In the context of Global Value Chain governance, Indonesian incubation model showed tendencies toward relational governance. The type of relation was complex and interdependent. This condition has pushed the emergence of Godfather actor who had specific competences that sustain innovation.